SEN1 TEA'TER SERA - Satoto, Soediro (LPMPP Universitas Negeri Yogyakarta, 2001)
There is an impression that Theatre looks like an 'illegitimate child' There 19 no I'heatreClass but Drama in the formal educational institutions of non-art departments The discussionin the learning process of Drama is not going up to Theatre 'I'here is no research on Theatre in .thesis and dissertation It can be found that only some of the formal educational institutions ofart deparltnents wh ch has Department that arranges a 'Theatre Class and Subject of 'TheatreYet, they both are only matter of choice, and cons deredn othing more than a material ofart creation or art analysis Meanwhile, the Theatre groups do not consider them as a scientifictidy, but as a result of the creative process of writing dramatic text and transferring it intoperformance text on stage as performing art (theatrical production) Theatre has been 'placed'so far fro111 Drama, and even in the educational institution of non-art department, Theatre hasbeen lefi in the process of learning Drama 'untouched' Moreover, as a collective art, Theatrepresents the implementation of Drama In the process of learning Drama, Theatre maycontribute various educational values. In other words, The Theatre constitutes a media ofEducation in school. That is why the assumption that Theatre 'placed' beyond the field ofLiterature and Drama studies cannot be accepted